Revisão anatômica e osteológica de Parotocinclus maculicauda (Steindachner, 1877) (Loricariidae: Hypoptopomatinae) - Cavalet, Elenita (Universidade do Vale do Rio dos Sinos, 2014)
The family Loricariidae comprises the largest number of described species of catfishes with approximately 872 valid species , the largest family of world fish fauna. The Hypoptopomatinae subfamily comprises 20 genera and 136 species are recognized as monophyletic . However , the monophyly of the genus Parotocinclus, is being challenged . Phylogenetic studies claim that Parotocinclus occupies a more basal position within Otothyrini tribe. In a more recent hypothesis of the phylogeny of the subfamily, was not found support for the monophyly of Otothyrini tribe and Parotocinclus was recognized as a genera gathering a complex of highly polyphyletic species. Currently , Parotocinclus joins 28 valid species. Parotocinclus maculicauda (type species of the genus) is found in coastal rivers from Santa Catarina to the Espirito Santo states . It is characterized by the presence of bony plates, pectoral girdle exposed supporting odontodes , the presence of adipose fin and dorsal and pectoral fins slightly reddish . Was sexually dimorphic, males with visible genital papilla, a projection of skin at the base of the spine in the pelvic fin. The skeleton of P. maculicauda presents a high degree of mergers and downsizing in many bony structures. The analysis of external and internal characters and their comparison between different loricaiid species, as well as the configuration of the bones and associated pectoral girdle and skull muscles, are considered in the survey of morphological information at different levels within the family Loricariidae.m
Review anatomical and osteological of Parotocinclus maculicauda, (Steindachner, 1877) (Loricariidae: Hypoptopomatinae)
Keywords: Ictiofauna; Taxonomia; Neotropical; Peixes de água doce; Cascudinhos; Ichthyofauna; Taxonomy; Freshwater fish; Catfishes; ACCNPQ::Ciências Biológicas::Biologia Geral